Names and Titles: Maiden Name Retention and the Use of Ms. - Atkinson, Donna L. (Linguistica Atlantica, 1987)
This sociolinguistic study examines the two dependent variables of stereotypes of women who use Ms., and stereotypes of women who retain their maiden name after marriage, with respect to the five independent variables of sex, age, level of education, degree of religiousness, and feminist orientation. Three hypotheses are proposed and are tested by means of a questionnaire distributed to a stratified sample of 325 subjects. The data from the sample are analyzed using the SPSS subroutines Analysis of Variance and Pearson Correlation and the results indicate that subjects’ sex, level of education, and degree of religiousness are significant with respect to their stereotypes. A strong positive correlation is shown between stereotypes of women who retain their maiden name and stereotypes of women who use Ms .